Analysis of the Ethics Buying and Selling Used Goods on Facebook Marketplace in the Perspective of the Qur'an - Suriadi; Ahmad Yasir; Malfiandri (Al-Hukumah: Jurnal Ilmu Pemerintahan dan Studi Islam, 2026)
The practice of buying and selling used goods constitutes an important subject in Islamic muamalah studies, particularly in relation to ethical compliance in transactions. Problems often arise from unclear contract processes and the neglect of established Islamic business ethics, such as the absence of khiyar rights between sellers and buyers, which may lead to unfair outcomes, including the inability to return purchased goods. These issues become more complex in the context of digital transactions, where the potential for loss is higher due to limited direct interaction between parties. This study aims to examine and apply the ethical values of buying and selling as outlined in the Qur’an to the practice of online transactions involving used goods, specifically within the Facebook Marketplace platform. This research employs a qualitative approach using a library research method, focusing on normative analysis. Data are collected from primary sources, including Qur’anic verses related to transaction ethics such as honesty, justice, and the prohibition of fraud, as well as relevant hadith. Secondary sources include fiqh muamalah literature, Islamic business ethics references, and scholarly articles on online marketplaces and consumer protection. Data analysis is conducted using descriptive-analytical and thematic interpretation approaches. The findings indicate that the majority of Islamic scholars (jumhur ulama) agree that buying and selling used goods is permissible (mubah), provided that transactions are conducted honestly, transparently, and in accordance with Islamic ethical principles. Thus, the application of Qur’anic values is essential in ensuring fairness and trust in digital marketplace transactions.